CEO Type and Firm Performance: Evidence from Nasdaq Baltic - Voveris, Donatas (Ekonomika, 2024)
Despite the well-established characteristics of shareholder-CEOs and professional-CEOs, previous research has yielded inconclusive findings on the actual impact of the separation of shareholding and management on firm financial performance. This study aimed to address this gap by going off the beaten path of research centered on the U.S.-listed firms and investigating 55 firms listed on the Nasdaq Baltic market in the post-Soviet countries of Estonia, Latvia, and Lithuania from 2017 to 2021. While professional-CEO-led firms displayed higher Tobin’s Q (M = 1.37) compared to shareholder-CEO-led firms (M = 1.17), and shareholder-CEO-led firms had a higher average ROE (M = 7.76%) compared to professional-CEO-led firms (M = -1.74%), independent samples t-test analysis revealed that these differences in either stock market performance (p = .250 > .05) or shareholder return (p = .193 > .05) were statistically insignificant. These findings challenge organizational life cycle theory and agency theory predictions, aligning instead with stewardship theory and upper echelons theory, suggesting that CEO characteristics, motivation, and actions, while clearly distinct for shareholder-CEOs and professional-CEOs, are not the sole determinant of financial performance in mature firms. Accordingly, shareholder-CEOs, other stockholders, and boards of directors should draw support from these findings in their considerations regarding firm leadership.
Keywords: Shareholder-CEO; Professional-CEO; Firm performance; Agency theory; Organizational life cycle theory; stewardship theory